2018
DOI: 10.14419/ijet.v7i4.15149
|View full text |Cite
|
Sign up to set email alerts
|

Integrated-system to minimizing cyber harassment in kingdom of Saudi Arabia (KSA)

Abstract: The proposed system framework consists two main databases: Lexicon dictionary and Summarized previous cases, by depending on Senti-ment analysis and N-Gram algorithms to match the terms and documents. In the first branch, the judge opens the cyber case and therefore the system will highlight the technical terms automatically. Furthermore, the technical terms matched with Lexicon dictionary will be high-lighted. After that, the judge opens the highlighted terms (as links), and description page will be appeared.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There is a need to incorporate SM as an indispensable tool in the academic field due to positive perception entrenched in students [55]. The findings guide the academic institution to integrate SM tools while probing new ways of impacting the opinion of the teachers and students [33]. Perception is shaped by individual attitudes.…”
Section: Attitude Toward Use (At)mentioning
confidence: 89%
See 2 more Smart Citations
“…There is a need to incorporate SM as an indispensable tool in the academic field due to positive perception entrenched in students [55]. The findings guide the academic institution to integrate SM tools while probing new ways of impacting the opinion of the teachers and students [33]. Perception is shaped by individual attitudes.…”
Section: Attitude Toward Use (At)mentioning
confidence: 89%
“…The different ways of communicating with others via knowledge sharing are highlighted by the increasing use of SM [1,30]. Moreover, the issue of the experience related to the use SM network has been studies by many researchers who found out that there is a significant relationship among collaborative authoring, learning outcomes, experience for collaborative learning, and resource sharing [31,32,33]. On the light of the discussion above, the flowing hypothesis was generated to be examined: H1: RS and EU are significantly related to each other.…”
Section: Resource Sharing (Rs)mentioning
confidence: 99%
See 1 more Smart Citation